Association of Daily Step Count and Multiple Sclerosis: An Accelerometer-Based Prospective Cohort Study (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: To date, no study has examined the dose–response association between daily step count and the incidence of Multiple Sclerosis (MS), and no specific step-based guidelines exist for MS prevention. This study aimed to investigate the association between accelerometer-derived daily step count and MS incidence in a large population-based cohort from the United Kingdom (UK). Methods: We used data from the UK Biobank cohort, including participants aged 40–79 years at baseline (2013–2015) who agreed to wear a wrist-worn triaxial accelerometer (Axivity AX3) for seven days. Daily step counts were estimated using the Verisense step-count algorithm implemented via the GGIR R-package. Incident MS cases were ascertained based on primary care and hospital inpatient data, as well as self-reported data. Cox proportional hazards models, with age as the timescale, were used to examine the association between step count and MS risk, adjusting for potential confounders. Daily step counts were analysed as a continuous variable (per 1,000 steps/day), in categories (